THE EFFECT OF E-SERVICE QUALITY, BRAND IMAGE, AND PROMOTION ON INTEREST IN BUYING PREMIUM SERVICES ON APPLICATIONS STREAMING MUSIC SPOTIFY ON STUDENT OF THE FACULTY OF ECONOMICS AND BUSINESS UNIMAL - Nadya Restianda; Sapna Biby; Naufal Bachri; Muchsin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine how the influence of e-service quality, brand image, and promotion on the interest in buying premium services on the Spotify music streaming application in students of the Faculty of Economics and Business, Malikussaleh University. The buying interest indicators used consist of transactional interest, referential interest, preferential interest, and exploratory interest. Then the e-service quality indicators used consist of efficiency, fulfillment of needs, system availability, privacy, speed of response, compensation, and service contact. Furthermore, brand image indicators consist of brand identity, brand personality, brand association, brand attitude and behavior, and brand benefits and advantages. The promotion indicators used consist of advertising, sales promotion, personal selling, public relations, and direct marketing. Where all these variables will be used using the Likert scale. The data used in this study is primary data obtained by distributing questionnaires to 210 students of the Faculty of Economics and Business, Malikussaleh University consisting of 5 majors or study programs. The data analysis technique used in this study is multiple linear regression analysis using the help of SPSS software version 26. The results showed that e-service quality, brand image, and promotion partially had a positive and significant effect on the interest in buying premium services on the Spotify music streaming application in students of the Faculty of Economics and Business, Malikussaleh University.